Similar outcome of tricuspid valve repair and replacement for isolated tricuspid infective endocarditis. Issue 6 (June 2022) - Di Mauro, Michele; Bonalumi, Giorgia; Giambuzzi, Ilaria; Dato, Guglielmo Mario Actis; Centofanti, Paolo; Corte, Alessandro Della; Ratta, Ester Della; Cugola, Diego; Merlo, Maurizio; Santini, Francesco; Salsano, Antonio; Rinaldi, Mauro; et al.
Abstract : Aims: To compare early and late mortality of acute isolated tricuspid valve infective endocarditis (TVIE) treated with valve repair or replacement. Methods: Patients who were surgically treated for TVIE from 1983 to 2018 were retrieved from the Italian Registry for Surgical Treatment of Valve and Prosthesis Infective Endocarditis. All the patients were followed up by means of phone interview or calling patient referral physicians or cardiologists. Kaplan–Meier method was used to assess late survival and survival free from TVIE recurrence with log-rank test for univariate comparison. The primary end points were early mortality (30 days after surgery) and long-term survival free from TVIE recurrence. Results: A total of 4084 patients were included in the registry. Among them, 149 patients were included in the study. Overall, 77 (51.7%) underwent TV repair and 72 (48.3%) TV replacement. Early mortality was 9% (13 patients). Expected early mortality according to EndoSCORE was 12%. The TV repair showed lower mortality and major complication rate (7% and 16%), compared with TV replacement (11% and 25%), but statistical significance was not reached. Median follow-up was 19.1 years (14.3–23.8). Late deaths were 30 and IE recurrences were 5. No difference in cardiac survival free from IE was found between the two groups after 20 years (80 ± 6% Repair Group vs 59 ± 13% Replacement Group, P = 0.3). Conclusions: Overall results indicate that once surgically addressed, TVIE has a low recurrence rate and excellent survival, apparently regardless of the type of surgery used to treat it.